Mendelian randomization study on the causal effects of COVID‐19 on childhood intelligence. Issue 7 (31st March 2022) - Zhu, Gaizhi; Zhou, Shan; Xu, Yaqi; Gao, Ran; Li, Huan; Su, Wenting; Han, Gencheng; Wang, Renxi
Abstract: Although individuals with coronavirus disease 2019 (COVID‐19) are known to be at increased risk for other conditions resulting from pathogenic changes (including metaplastic or anaplastic) in the lungs and other organs and organ systems, it is still unknown whether COVID‐19 affects childhood intelligence. The present two‐sample Mendelian randomization study aims to identify the genetic causal link between COVID‐19 and childhood intelligence. Four COVID‐19 genetic instrumental variants (IVs) were chosen from the largest genome‐wide association studies (GWAS) for COVID‐19 (hospitalized vs. population) (6406 cases and 902 088 controls of European ancestry). The largest childhood intelligence GWAS ( n  = 12 441 individuals of European ancestry) was used to evaluate the effect of the identified COVID‐19‐associated genetic IVs on childhood intelligence. We found that as the genetic susceptibility to COVID‐19 increased, childhood intelligence followed a decreasing trend, according to mr_egger ( β  = −0.156; p  = 0.601; odds ratio [OR] = 0.856; 95% confidence interval [CI]: 0.522–1.405), simple mode ( β  = −0.126; p  = 0.240; OR = 0.882; 95% CI: 0.745–1.044), and weighted mode ( β  = −0.121; p  = 0.226; OR = 0.886; 95% CI: 0.758–1.036) analyses. This trend was further demonstrated by the weighted median ( β  = −0.134; p  = 0.031; OR = 0.875; 95% CI: 0.774–0.988) and the inverse variance weighted ( β  = −0.152; p  = 0.004; OR = 0.859; 95% CI: 0.776–0.952). Our analysis suggests a causal link between genetically increased COVID‐19 and decreased childhood intelligence. Thus, COVID‐19 may be a risk factor for declines in childhood intelligence.